Medial Patellofemoral Ligament Repair with Suture Tape Augmentation Can Yield Good Midterm Clinical Outcomes Regardless of Skeletal Maturity and Joint Laxity - Shinichiro Takada; Hirotaka Nakashima; Keisuke Nakayama; Soshi Uchida (Biomimetics)
While several studies have reported short-term clinical outcomes after medial patellofemoral ligament (MPFL) repair with suture tape augmentation, there is still a dearth of knowledge regarding midterm clinical outcomes. This study aimed to evaluate the midterm clinical outcomes of MPFL repair with suture tape augmentation in patients with patellar dislocation. We retrospectively reviewed the clinical records of patients who underwent MPFL repair with suture tape augmentation for at least one episode of patellar dislocation between 2015 and 2020. Patient-reported clinical outcomes (PROs) were evaluated via the International Knee Documentation Committee (IKDC) score and the knee injury osteoarthritis outcome score (KOOS). In total, 17 knees (4 males and 13 females) who underwent MPFL repair with suture tape augmentation with a mean follow-up of 54.6 ± 19.5 months were included in this study. PROs significantly improved from preoperatively to the final follow-up (IKDC score: 50.7 ± 26.6 vs. 88.8 ± 13.0, p < 0.001; KOOS: 68.8 ± 23.3 vs. 91.2 ± 8.4, p = 0.011) without reducing the patient’s activity level at the final follow-up (UCLA AS score: 7.9 ± 2.4 at preinjury vs. 7.9 ± 2.2 at the final follow-up, p = 0.655). Subgroup analysis revealed good postoperative outcomes, regardless of the patient’s skeletal maturity or the presence or absence of generalized laxity. In conclusion, MPFL repair with suture tape augmentation is a safe and effective treatment for midterm follow-up.